Energy flow models for the estimation of technical losses in distribution network - Au M.T.; Tan C.H. (Institute of Physics Publishing, 2023)
This paper presents energy flow models developed to estimate technical losses in distribution network. Energy flow models applied in this paper is based on input energy and peak demand of distribution network, feeder length and peak demand, transformer loading capacity, and load factor. Two case studies, an urban distribution network and a rural distribution network are used to illustrate application of the energy flow models. Results on technical losses obtained for the two distribution networks are consistent and comparable to network of similar types and characteristics. Hence, the energy flow models are suitable for practical application. Published under licence by IOP Publishing Ltd.